PROFESSIONALLY INFERRED TRUST: HOW TRUST DEVELOPS IN TEMPORARY PROFESSIONAL TEAMS - Rani OKHOMINA (PT. Antis International Publisher, 2026)
Objective: Trust is widely recognised as a critical determinant of team effectiveness, collaboration, and organisational performance. However, most trust research has focused on stable, long-term teams where relationships develop through repeated interaction over time. Far less is known about how trust emerges in temporary professional teams that must perform effectively despite limited opportunities for relationship development. This study explores how trust is established, maintained, and influenced by leadership in temporary project teams of business psychologists compared with permanent operational teams. Method: A qualitative comparative design was employed. Semi-structured interviews were conducted with nine participants drawn from temporary project teams of business psychologists and permanent operational teams within the same organisational context. Data were analysed using reflexive thematic analysis following Braun and Clarke's (2006, 2021) six-phase approach. Results: The findings suggest that trust develops through distinct mechanisms across team structures. In temporary teams, trust was established primarily through perceptions of competence, professional credibility, role clarity, and leadership signalling rather than interpersonal familiarity. Trust functioned as a professional working assumption that enabled collaboration despite limited relational history. In permanent teams, trust emerged gradually through repeated interactions, behavioural consistency, and accumulated relational experiences. Leadership played a critical role in both contexts by creating predictability, clarity, and psychological security. However, the specific leadership behaviours required differed according to team temporality. Novelty: This study addresses a gap in the trust literature by examining how trust develops within temporary professional teams, a context that has received limited scholarly attention relative to stable, permanent teams. It introduces the concept of professionally inferred trust, whereby professional signals such as expertise, credibility, and role clarity serve as active substitutes for relational history during the early stages of collaboration. This extends Swift Trust Theory by proposing a more deliberate inferential process than passive suspension of uncertainty, and complements McAllister's (1995) cognition-based trust framework by identifying a mechanism that operates prior to behavioural evidence becoming available. The findings have implications for how organisations design, lead, and support temporary project teams in knowledge-intensive environments.